LEGAL STATE OF INTERSTATE AND INTERGOVERNMENTAL REGULATORY LEGAL ACTS ON ENSURING ECOLOGICAL SAFETY OF SPACE ACTIVITIES OF THE BIKONUR COMPLEX (Journal of actual problems of jurisprudence, 2019)
In this article the author searching the agreements between governments about environmental aspects of space activity, also making somerecommendations for their developing and realization.